Adoption unfiltered : revelations from adoptees, birth parents, adoptive parents, and allies - Easterly, Sara; Vander Vliet Ranyard, Kelsey; Holden, Lori, 1962- (Rowman & Littlefield Publishers, 2024)
"Adoption is a multi-sided experience that can feel like it takes place in a vacuum. Here, three participants in the adoption triad reveal the challenges, the triumphs, and everything in between from their perspectives of adopted, adopter, and birth parent, and those of others who have experienced adoption from a variety of perspectives and roles"--